DOMESTIC AND FOREIGN EXPERIENCE OF STATE SUPPORT OF SMALL ENTERPRENEURSHIP DEVELOPMENT - V.P. Petrenko (Економіка та право, 2018)
Main principles of state strategic management of small entrepreneurship development in USA, Great Britain, Germany, Fran ce and EU member states are investigated in the article. The role of small entrepreneurship in the economy of various countries is investigated. Main aims and principles of small entrepreneurship support in the developed countries are stated, main mechanisms for small entrepreneurship development in Europe are outlined. Moreover, main directions of state strategy of the small business development in each of the listed countries are determined. The role of the operation of small beneficiaries in the economy formation in the certain region and in the country en at large is substantiated, and the necessity of the development of state strategy of small business development in the immediate perspective was determined. The necessity of the change of strategic priorities of small business development on the state level in Ukraine is justified based on the considered world experience. Main strategic priorities of the state support of small entrepreneurship development in Ukraine for economic rise of the state regions, state at large and population employment is developed. The consequences of the influence of eurointegration processes on small entrepreneurship development in Ukraine are determined, the proposals on activation of its development are scientifically justified. The global experience of small entrepreneurship development (that is part of competitive, dynamic, intellect-intensive economy, which influences stable economic growth, increase of workplace numbers and population welfare) is investigated. The status if small entrepreneurship in Ukraine is analyzed, the factors which influence it negatively are determined, a package of measures for support of small entrepreneurship development (including: streamlining of the simplified tax system, formation of modern financial infrastructure for small entrepreneurship development, formation of favourable business climate, legal support of the entrepreneurship) is proposed.